2022
DOI: 10.3390/su14095577
|View full text |Cite
|
Sign up to set email alerts
|

Philopatry as a Tool to Define Tentative Closed Migration Cycles and Conservation Areas for Large Pelagic Fishes in the Pacific

Abstract: Migrations of large pelagic fishes across the Pacific are usually inferred from tagging or genetic studies. Even though these techniques have improved over time, they still fail to demonstrate large transoceanic migrations, usually proposing ‘routes’ that do not cycle seasonally. The current study uses the concept of ‘philopatry’ in 11 large pelagic fish species, i.e., the tendency for animals to return to their natal site to reproduce. Tentative migration routes and maps emerge by applying this concept to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Our results can be used as steppingstone for the design and implementation of national and regional management policies rigorously complied by all members of IATTC, which should be linked to conservation efforts like the recent expansion of the Galápagos Marine Reserve and the establishment of the Galápagos-Cocos Swimway, a marine corridor that protect species as they migrate between protected areas. Boerder et al [ 72 ] implied that the Galápagos Marine Reserve has a net positive effect on pelagic fisheries associated to the archipelago, emphasizing the importance of large-scale marine protected areas as both fisheries management and biodiversity conservation tools [ 73 ]. Additionally, Orange [ 55 ] suggested that the area around the Galápagos Islands is a spawning area for yellowfin tuna, which should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Our results can be used as steppingstone for the design and implementation of national and regional management policies rigorously complied by all members of IATTC, which should be linked to conservation efforts like the recent expansion of the Galápagos Marine Reserve and the establishment of the Galápagos-Cocos Swimway, a marine corridor that protect species as they migrate between protected areas. Boerder et al [ 72 ] implied that the Galápagos Marine Reserve has a net positive effect on pelagic fisheries associated to the archipelago, emphasizing the importance of large-scale marine protected areas as both fisheries management and biodiversity conservation tools [ 73 ]. Additionally, Orange [ 55 ] suggested that the area around the Galápagos Islands is a spawning area for yellowfin tuna, which should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an equal and respectful co-production of knowledge about marine ecosystems will improve participation in MPA management at a global level. Adding non-conventional knowledge to other initiatives that are mainly based on literature reviews, as in the case of so-called 'blue corridors' [45], will improve the connectivity of the habitats used by the exploited species, and ultimately improve the prospects of food security.…”
Section: Discussionmentioning
confidence: 99%
“…We then averaged biomass values for each yellowfin tuna population across ten years to match the BRUVS dataset. The stock assessments compiled here assume a single yellowfin tuna stock for each tuna RFMO, although distinct spawning areas and genetic differences may imply individual stocks or significant heterogeneity in yellowfin tuna distributions (Pecoraro et al, 2018;Vincent et al, 2020;Muñoz-Abril et al, 2022;Relano and Pauly, 2022).…”
Section: Rfmo Fishery Data and Stock Assessment Compilationmentioning
confidence: 99%